Synergizing AI, Machine Learning, Optoelectronics, and Computational Tools for Sustainable Wireless Communication Systems - Naeema Nazar , Divya Nair , Krishnendu P S , Pimmy Mathews , Dr. Saju A (South Eastern European Journal of Public Health, 2025)
The need for sustainable wireless communication systems has become increasingly critical in the face of growing global demand for energy-efficient and high-performance tech- nologies. This paper examines the integration of artificial intelligence (AI), machine learning, optoelectronics, and computational tools to enhance the design and optimization of such systems. AI and machine learning techniques offer powerful methods for optimizing system performance through predictive analytics and dynamic adaptation. Optoelectronic technologies, with their ability to enable high-speed, low-power data transmission, play a key role in addressing the limitations of conventional electronics. Additionally, computational tools are essential for modeling, simulation, and optimization, allowing for precise evaluation of complex communication networks. By leveraging the combined potential of these technologies, the paper demonstrates how sustainable wireless communication systems can be developed to meet both performance and environmental goals. The proposed framework outlines a comprehensive approach to achieving energy-efficient, scalable, and reliable communication solutions for the future.